Bureaucratized Scientific Knowledge Production in the Area of Social Work within the Context of Neoliberalism: Investigation of Master’s Theses Research - Canan Neşe Kınıkoğlu; Caner Özdemir (Sosyal Siyaset Konferansları Dergisi)
This paper investigates the knowledge production in social work through document analysis of the master’s theses, the primary step in professional and academic expertise, within the context of the neoliberalization of higher education in Turkey. Focusing on the period between 2005 and 2020, when the field of social work expanded in universities in Turkey, this paper poses the questions related to what social work master’s theses’ numbers, subjects, methods, and cases are, as well as how they are changing. To this end, a total of 674 open access master’s theses completed in the departments of social work, social services, and social work policies and management were examined through their abstracts and full texts. The number of masters’ thesis in social work skyrocketed after 2016, in line with the escalating number of post-graduate programs in social work in Turkey. The findings of the study reveal that this quantitative increase does not bring along a qualitative improvement in knowledge production in social work. The majority of the examined theses do not meet the basic methodological requirements of scientific knowledge, such as the correct definition and explanation of the population and sampling techniques of the study. These theses are further limited to the national scale since they mostly focus on the central regions of Turkey, such as Ankara and Istanbul, and they are differentiated nly by the micro contexts and the different subject matters they study. Thus, on one hand, knowledge production in social work at the master’s level has expanded while moving away from the foundations of scientific knowledge. On the other hand, it has been bureaucratized through limited research scopes and standardized thesis writing processes, yielding the conclusion that it has transformed into a mass production process.